I want to break free: How a design approach guides nascent intrapreneurs in a global public service organisation - Antonius van den Broek; Mikko Koria; Emilia Saarelainen (Journal of Innovation and Entrepreneurship, 2023)
In this paper, we expand our understanding of how a design approach can enable and guide employees to break free from their incumbent mindset and ways of working and become intrapreneurs in public organisations. While previous studies have identified desired behaviour for intrapreneurs, there is a lack of understanding how new intrapreneurs adapt such behaviours, especially in public organisations. This paper shows how the readily available approaches of design practice can guide new intrapreneurs to break free from their routines, adopt entrepreneurial behaviours and provide the practical tools to help them to persuade others to collaborate with them on their innovative ideas. We draw from 19 interviews with nascent intrapreneurs, and documentation collected at the UN Refugee Agency to inductively develop a model for how design supports employees in their journey to become an intrapreneur. Our findings illustrate how adopting a design approach provided aspiring intrapreneurs to become ambidextrous in navigating between the creative and the calculative logics and heuristics in highly structured organisations. Both the design attitude and the tools associated with design practice helped new intrapreneurs to adopt an entrepreneurial mindset, position their new ideas and align them to the needs, priorities and constraints of colleagues and stakeholders.
Keywords: 650; Design; Intrapreneurial behaviour; Intrapreneurship; Nascent intrapreneurs